CONSUMPTION OF SEXUALLY EXPLICIT MATERIALS AMONG ADOLESCENTS: DO PARENTING STYLES OR CHILD REARING PATTERNS MATTERS - JAIN, SAMIKSHA; PANDEY, NEELAM (International Journal of Psychosocial Rehabilitation, 2020)
The term pornography has been coined from two Greek words, “porni” means prostitute and “graphein” means to write. That means, pornography is “representation of the action of prostitutes”. Check & Guloine (1989) has termed it “Sexually Explicit materials”. This case report attempts to understand the experiences, factors and consequences of the adolescents who are exposed to such material during their childhood. Two participants were interviewed personally for the study, aging 18 years, residing in Delhi NCR currently but belong to different part of the country, India. It became evident through an analysis that male and female both have the equal exposure of such content because of the availability and accessibility of the resources. Among males, it was found that the need to involve themselves into such content were curiosity, maladaptive behaviours, youthful appearance in an old person, balancing life, stress and many more. Whereas among females, platform to express emotions, urge to fulfil bodily sensation, pleasurable feeling etc. The most important and common facet among young male and female is the hazardous practices at the safe place which is the role of parenting and the relationship matters which has influenced upon the exposure of adolescence towards sexually explicit materials.